Design and development of an autonomous underwater vehicle - Tay, Jia Min (2019)
Computational Fluid Dynamics (CFD) was used in this report to determine the hydrodynamic characteristics and operating points of an Autonomous Underwater Vehicle (AUV) design. The effect of thrusters was simulated using a momentum source term, and its effect was tested using two computational models, k-ω SST and Spalart-Allmaras. A water tunnel test was done to determine the effect of the thrusters used in the design of this AUV, Blue Robotics T200. The results obtained from the water tunnel test was combined with the drag results obtained from CFD to obtain the operating points of the AUV in all three directions.